2023
DOI: 10.1021/acsmaterialslett.2c01198
|View full text |Cite
|
Sign up to set email alerts
|

Cation Substitution-Induced Partial Inversion to Pervade Short-Wave Infrared Light for Improving the Accuracy of Artificial Intelligence Image Recognition System

Abstract: Short-wave infrared (SWIR) light is suitable for image recognition and biomedical applications due to the ability to perform unique absorption of material components. In this study, the partial inversion of a spinel structure was modified through cation substitution to induce an inverse behavior and charge variation. For MgGa 2 O 4 , the substitution of Ga 3+ with Sn 4+ expanded lattice parameters (a, b, c, and V), and Mg 2+ was used to achieve charge balance. When the concentration of Sn increased, the T 2g v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…However, the typical Ni 2+ excitation sources such as 808/980 nm lasers and ultraviolet (UV)/near UV chips are energy-inefficient, suffering from low quantum efficiency. , Wang et al reported a series of Cr 3+ /Ni 2+ codoped NIR phosphors Zn 1+ y Sn y Ga 2–2 y O 4 with a Ni 2+ emission intensity that can be enhanced by 450 nm blue light excitation, achieved through Cr 3+ –Ni 2+ electric dipole–dipole interactions, opening a new approach for NIR-II phosphor design. Single Cr 3+ to Ni 2+ energy transfer has been reported widely, with an internal quantum efficiency (IQE) of approximately 50%, , with a higher IQE of approximately 70% reported through energy transfer from Cr 3+ –Cr 3+ ion pairs to Ni 2+ . Notably, the most efficient Cr 3+ –Ni 2+ energy transfer in the Zn 1+ y Sn y Ga 2–2 y O 4 phosphor series codoped with Cr 3+ /Ni 2+ was found for compositions with an intermediate spinel-type structure, found between normal and inverse spinel-type structures .…”
Section: Introductionmentioning
confidence: 98%
“…However, the typical Ni 2+ excitation sources such as 808/980 nm lasers and ultraviolet (UV)/near UV chips are energy-inefficient, suffering from low quantum efficiency. , Wang et al reported a series of Cr 3+ /Ni 2+ codoped NIR phosphors Zn 1+ y Sn y Ga 2–2 y O 4 with a Ni 2+ emission intensity that can be enhanced by 450 nm blue light excitation, achieved through Cr 3+ –Ni 2+ electric dipole–dipole interactions, opening a new approach for NIR-II phosphor design. Single Cr 3+ to Ni 2+ energy transfer has been reported widely, with an internal quantum efficiency (IQE) of approximately 50%, , with a higher IQE of approximately 70% reported through energy transfer from Cr 3+ –Cr 3+ ion pairs to Ni 2+ . Notably, the most efficient Cr 3+ –Ni 2+ energy transfer in the Zn 1+ y Sn y Ga 2–2 y O 4 phosphor series codoped with Cr 3+ /Ni 2+ was found for compositions with an intermediate spinel-type structure, found between normal and inverse spinel-type structures .…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, short wavelength study has become popular because of its high penetration power and characteristic absorption signal. Specifically, those capable of emitting light in the short wavelength infrared (SWIR) range of 1000–1700 nm are increasingly essential for advanced technological applications. This spectral region, often called the “eye-safe” region, is also crucial for light detection and ranging (LiDAR) applications where safety considerations for incidental human exposure are vital. In biomedical diagnostics, emissions beyond 1000 nm allow for deeper tissue penetration with reduced scattering, enhancing the capabilities of non-invasive optical imaging and improving diagnostic accuracy. …”
Section: Introductionmentioning
confidence: 99%
“…1−7 In recent years, numerous applications have derived from NIR light with an emission range of 700−1,000 nm to SWIR light, starting from basic night vision technology to biomedical imaging applications, and recently, it has even been able to be a great light source of artificial intelligence image recognition system to improve its accuracy. 5 Nowadays, it has been a trend that NIR emission phosphor material combines with light emitting diodes (LEDs) because of its advantages of being inexpensive, highly efficient, and compact, which are the reasons for its suitability as reliable light sources. Therefore, modifying phosphor materials to achieve enhanced broadband SWIR light is essential in order to obtain better performance in LED applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Short-wave infrared (SWIR) light, with an emission range of 1,100–1,700 nm, belongs to near-infrared (NIR) light. SWIR light has drawn lots of attention owing to its advantages of high penetration and even can penetrate through biological tissues innocuously. In recent years, numerous applications have derived from NIR light with an emission range of 700–1,000 nm to SWIR light, starting from basic night vision technology to biomedical imaging applications, and recently, it has even been able to be a great light source of artificial intelligence image recognition system to improve its accuracy . Nowadays, it has been a trend that NIR emission phosphor material combines with light emitting diodes (LEDs) because of its advantages of being inexpensive, highly efficient, and compact, which are the reasons for its suitability as reliable light sources.…”
Section: Introductionmentioning
confidence: 99%